Stable silicon anodes realized by multifunctional dynamic cross-linking structure with self-healing chemistry and enhanced ionic conductivity for lithium-ion batteries. (August 2022) - Wan, Xin; Mu, Tiansheng; Shen, Baicheng; Meng, Qi; Lu, Guangchong; Lou, Shuaifeng; Zuo, Pengjian; Ma, Yulin; Du, Chunyu; Yin, Geping
Abstract: Silicon anodes have attracted enormous attention with the merits of outstanding theoretical capacity for high-energy-density lithium-ion batteries. However, the drastic volume variation will destroy the structural integrity of the electrode system during the alloying/dealloying process. Herein, based on the supramolecular self-assembly, a multifunctional dynamic cross-linking strategy with self-healing chemistry and enhanced ionic conductivity for silicon electrode network structure is rationally designed by amino-functionalized silicon (Si-NH2 ) and dopamine-modified poly(acrylic acid) (PAA-DA). Dynamic reversible hydrogen bonds and ionic bonds are formed by random cross-linking of the primitives carried by the material, which endow the electrode with rapid self-healing ability and strong adhesion, and provide a continuous internal pathway for the electrode system. Moreover, the presence of polar groups can beneficially heighten the transport kinetics of lithium ions. The prepared Si-NH2 @PAA-DA electrode displays excellent high-rate capability with a reversible capacity of 2671.6 mAh g −1 at 1 C (1 C = 4000 mA g −1 ) and superior cycle stability (2160.1 mAh g −1 after 100 cycles at 400 mA g −1 ). Therefore, this design idea with dynamic reversible and multi-crosslink network structure provides in-depth insights for the advancement of the next-generation high-energy-density batteries. Graphical Abstract: ga1 Highlights: Multifunctional dynamic cross-linking strategy (Si-NH2 @PAA-DA) with self-healing chemistry and enhanced ionic conductivity for silicon electrodes is successfully designed. Multiple dynamic supramolecular interactions (hydrogen bond and ionic bond) can effectively dissipate the stress-energy of volume change and relieve the mechanical cracking of the electrode. The presence of polar groups can beneficially heighten the transport kinetics of lithium ions. Si-NH2 @PAA-DA electrode exhibits outstanding cycling stability and rate performance.